Anti-inflammatory and anti-oxidative effect of Korean propolis on Helicobacter pylori-induced gastric damage in vitro - Song, Moon-Young; Lee, Da-Young; Kim, Eun-Hee (The journal of microbiology, 2020)
Helicobacter pylori , present in the stomach lining, is a Gramnegative bacterium that causes various gastrointestinal diseases, including gastritis and peptic ulcers. Propolis is a natural resinous substance collected from a variety of plants, and contains several natural bioactive substances. The aim of this study was to investigate the anti-inflammatory and antioxidative effects of Korean propolis on H. pylori -induced damage in the human adenocarcinoma gastric cell line. The propolis used in this study was obtained from the Korea Beekeeping Association in South Korea. The expression of pro-inflammatory interleukins (ILs), such as IL-8, IL-12, IL-1β, tumor necrosis factor alpha, cyclooxygenase-2, and inducible nitric oxide synthase, which was increased after H. pylori infection, significantly decreased in a dose-dependent manner upon pretreatment with Korean propolis, because of the suppression of mitogen-activated protein kinases and nuclear factor kB pathway. The anti-oxidative activity of propolis was assessed using the 2,2-diphenyl-1-picrylhydrazyl hydrate free radical assay. Korean propolis showed significant anti-oxidative effects via reactive oxygen species scavenging. In addition, pretreatment with Korean propolis upregulated the expression of anti-oxidant enzymes through Nrf2 signaling activation. These findings indicate that the use of Korean propolis, which has anti-inflammatory and anti-oxidative effects, can be promising for the prevention of H. pylori -induced gastric damage.